Hubungan Keahlian dengan Partisipasi dan Hubungan Partisipasi dengan Variabel lain dalam Pengembangan Sistem Informasi - lindrianasari lindrianasari (The Indonesian Journal of Accounting Research, 2013)
Research in end-user information system participation findings in revealing how information systems strategy can be developed with the user involvement. Some conclusions indicate that end-user participation is significantly fruitful. However, to what extent end-user participation influences the success information system is a question of this study. In this case, it is argued that there are intervening and moderating variables in explaining the relationship between “end user participation” and the “success of information system development”. This study analyzes three variables as intervening variable: task uncertainty, system acceptance, and user satisfaction. The study also analyze expertise, as a variable can be stimulated end-user participation.The conclusion of this study supports the previous research conducted by many scholars in information systems. The survey involved 109 respondents from various kind of private and public institutions reveals that the “expertise” correlates positively in stimulating end-user “participation” in the process of building and improving information system. More over, it is also revealed that if the information system developed with the user, the system will be more accepted with in turn the user will be more satisfied in dealing with their job by using the information system developed.